FACTORS THAT INFLUENCE STUDENTS’ SAVING BEHAVIOR: FINANCIAL KNOWLEDGE AS AN INTERVENING VARIABLE - Feni Nuril Fatiha; Mardiana Mardiana (Journal of Management Small and Medium Enterprises (SMEs), 2025)
A new phenomenon known as doom spending has emerged as a result of the economic climate becoming more unpredictable. This leads to excessive spending, which in turn causes consumptive behavior. Consistent saving efforts, however, can reduce this. This study aims to investigate the influence of peer influence and parental socialization on the saving behavior of students at Universitas Islam Negeri (UIN) Maulana Malik Ibrahim Malang, utilizing financial knowledge as an intervening variable. Data was gathered via surveys or primary sources and processed with SmartPLS 3. Purposive sampling techniques were used to pick a minimum sample of 110 respondents. Based on data processing results, it can be concluded that while parental socialization has no discernible impact on saving behavior, peer influence does. The association between parental socialization and saving behavior can be mediated by financial knowledge, whereas the relationship between peer influence and saving behavior cannot be mediated by financial knowledge. Keywords: Doom Spending; Financial Knowledge; SavingBehavior; Peer Influence; Parental Socialization